Comparison of microscale sealed vessel pyrolysis (MSSVpy) and hydropyrolysis (Hypy) for the characterisation of extant and sedimentary organic matter - Berwick, Lyndon; Greenwood, Paul; Meredith, W.; Snape, C.; Talbot, H. (Elsevier, 2010)
Microscale sealed vessel pyrolysis (MSSVpy) and catalytic hydropyrolysis (Hypy) combined with gas chromatography-mass spectrometry have emerged in recent years as useful and versatile organic analytical and characterisation methods. Both now commercially available, these pyrolysis methods complement traditional flash pyrolysis analysis which can be limited by excessive degradation or inadequate chromatographic resolution of pyrolysates of high structural polarity. To assess the versatility and merits of these two pyrolysis methods they were separately applied to several organic samples reflecting different thermal maturities. This comparison revealed many product similarities, but also several important features unique to each.